Use of bacterial inoculant in rehydrated corn grain silage - Frederico Costa Nunes; Kátia Cylene Guimarães; Flávia Oliveira Abrão Pessoa; Felipe Pereira Cunha; Vitória Cassia Rafael de Souza Pereira; Tiago do Prado Paim; Patrick Bezerra Fernandes (Journal of Applied Animal Research)
The aim of this study was to evaluate the fermentative parameters and chemical compositions of corn grain silages rehydrated with different moisture levels, inoculated with bacteria (Lentilactobacillus hilgardii combined with Lentilactobacillus buchneri), and investigate the impact of this strategy on silage at different storage times. The study was carried out in the Animal Nutrition Laboratory, Rio Verde, Brazil. The experiment was carried out in a completely randomized design, in a triple factorial scheme, with six replications per treatment. At 30 and 40% moisture levels, the inoculant increased acidity. However, it was only at 35% moisture level that the inoculated silage achieved the pH within the appropriate range (4.16). In the silage without inoculant, the effluent loss was lower only in the silage with 30% moisture (9.11 g kg-1 DM). The presence or absence of the inoculant does not affect the concentration of crude protein and total carbohydrates. Rehydration with 35% moisture is recommended for quality silage production. Although the inoculant does not affect the chemical composition of the silage, its use is essential to ensure a proper fermentation process, preserve the quality and also to reduce nutrient losses during the moist grain silage preparation.